Right-sided infective endocarditis masquerading as pulmonary tuberculosis: a case report - Abdul Hadi, Azwanis; Khairuddin, Khairun’naim; Ismail, Nizamuddin (2021)
– Multiple visits to the health facilities (private clinic and government’s health clinic) and 2 hospital admissions in 2 months ■ Recurrent cough ■ Fever ■ Haemoptysis ■ LOW/LOA ■ Pleuritic chest discomfort during cough – Multiple course of oral antibiotic was given – TB and malignancy workout sent –negative – CXR showed lower zone hazzines